2021
DOI: 10.1037/neu0000668
|View full text |Cite
|
Sign up to set email alerts
|

Stronger impulse capture and impaired inhibition of prepotent action in children with ADHD performing a Simon task: An electromyographic study.

Abstract: Objective: A deficit in interference control is commonly reported in children with attention deficit hyperactivity disorder (ADHD). This has mainly been interpreted as a difficulty in inhibiting inappropriate responses. However, it could be due to at least two distinct and independent processes, which are often confounded: the activation or suppression of impulsive responses. The aim of the present study was to separate the contribution of these two processes. Method: We compared performance of 26 children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…On the other hand, by plotting interference effects against RT (known as a delta-plot), a reduction in the interference effect at the slower portion of the RT distribution should be observed, reflecting the efficiency of inhibitory control (Ridderinkhof, 2002;Ridderinkhof, 2002;Suarez, Vidal, et al, 2015;Van den Wildenberg et al, 2010;Van Wouve et al, 2016;Wylie et al, 2010Wylie et al, , 2013. Several studies using both non-clinical and clinical populations provide empirical support for this assertion (Burle et al, 2002;Grandjean et al, 2021b;Ridderinkhof et al, 2005;Suarez, Vidal, et al, 2015;Van Wouve et al, 2016;Wijnen & Ridderinkhof, 2007;Wylie et al, 2007;Wylie et al, 2009Wylie et al, , 2010aWylie et al, , 2010bWylie et al, , 2012Wylie et al, , 2013; for review, see Ridderinkhof et al, 2011;Van den Wildenberg et al, 2010) and have revealed that different manipulations could differently affect these two components of interference control (Fluchère et al, 2015;Grandjean et al, 2021aGrandjean et al, , 2021bRamdani et al, 2015).…”
Section: Reactive Inhibitory Control In the Simon Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, by plotting interference effects against RT (known as a delta-plot), a reduction in the interference effect at the slower portion of the RT distribution should be observed, reflecting the efficiency of inhibitory control (Ridderinkhof, 2002;Ridderinkhof, 2002;Suarez, Vidal, et al, 2015;Van den Wildenberg et al, 2010;Van Wouve et al, 2016;Wylie et al, 2010Wylie et al, , 2013. Several studies using both non-clinical and clinical populations provide empirical support for this assertion (Burle et al, 2002;Grandjean et al, 2021b;Ridderinkhof et al, 2005;Suarez, Vidal, et al, 2015;Van Wouve et al, 2016;Wijnen & Ridderinkhof, 2007;Wylie et al, 2007;Wylie et al, 2009Wylie et al, , 2010aWylie et al, , 2010bWylie et al, , 2012Wylie et al, , 2013; for review, see Ridderinkhof et al, 2011;Van den Wildenberg et al, 2010) and have revealed that different manipulations could differently affect these two components of interference control (Fluchère et al, 2015;Grandjean et al, 2021aGrandjean et al, , 2021bRamdani et al, 2015).…”
Section: Reactive Inhibitory Control In the Simon Taskmentioning
confidence: 99%
“…There are two possible explanations for this discrepancy. First, Ridderinkhof et al based their conclusions on analyses of delta plots for accuracy (including all types of trials), while we directly compared the accuracy rates for the INC trials at the fastest responses, which is a better indicator of impulse response, as suggested by Ridderinkhof himself in more recent articles (Van den Wildenberg et al, 2010) and as used in several more recent studies (Grandjean et al, 2021a;Ridderinkhof et al, 2011;Van Wouve et al, 2016;Wylie et al, 2012Wylie et al, , 2013. Second, a flanker task involves perceptive interference, whereas the Simon task involves motor interference.…”
Section: Adhd Affects Reactive Inhibitory Controlmentioning
confidence: 99%
“…This dual-systems perspective is also relevant to clinical populations with disorders in which impulsivity is dysregulated. For example, attention deficit hyperactivity disorder (ADHD) is characterized by inhibitory deficits, including increased impulsive action ( Schachar and Logan, 1990 ; Nigg, 2001 ; Wright et al, 2014 ; Grandjean et al, 2021 ). Impulsivity is also a key phenotype found in substance use disorder, in which both reward system and inhibitory dysfunctions are present ( Jentsch et al, 2014 ; Weafer et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%